VD_FINDINFO Jug / 2019 / 187 vom 17. Dezember 2018 - VD Tribunal cantonal (2018)
ABUS DE CONFIANCE, PEINE COMPLÉMENTAIRE, PRINCIPE DE LA CÉLÉRITÉ, UNITÉ DE LA PROCÉDURE | 138 ch. 1 CP, 49 al. 1 CP, 49 al. 2 CP, 5 CPP (CH)